Notice: Payments for answers will end 4/10/2017. Click for more info.
You have new items in your feed. Click to view.
Question and answer
Q: solve for x: show steps 8x + 4 = 4x – 4
A: 8x + 4 = 4x - 4 8x - 4x = - 4 - 4 4x = - 8 x = - 8/4 x = - 2
Expert answered|sharpies|Points 6553|
Question|Rated good
Asked 2/9/2012 5:16:24 PM
Updated 4/15/2014 1:50:22 PM
0 Answers/Comments
This answer has been confirmed as correct and helpful.
Edited by andrewpallarca [4/15/2014 1:50:20 PM]
Get an answer
New answers
Rating

There are no new answers.

Comments

There are no comments.

Add an answer or comment
Log in or sign up first.
Questions asked by the same visitor
solve for x with steps 4x – 4 + 3x = 3x + 5 – 5x
Weegy: 4x+3x-4=3x-5x+5 7x-4=-2x+5 7x+2x=5+4 9x=9 x=9/9 x=1 (More)
Question
Expert Answered
Updated 161 days ago|1/14/2018 4:01:28 PM
0 Answers/Comments
solve for x with steps 4( x – 2 ) = 5( x + 3)
Weegy: 9x (More)
Question
Expert Answered
Updated 4/15/2014 1:49:31 PM
2 Answers/Comments
4( x – 2 ) = 5( x + 3)
4x-8 = 5x+15
x = -23



Added 4/12/2014 5:16:26 PM
4( x – 2 ) = 5( x + 3);

4x-8 = 5x+15;

4x - 5x = 15 + 8;

-x = 23;

x = -23
Added 4/15/2014 1:49:31 PM
This answer has been confirmed as correct and helpful.
solve for x (show steps) 4( x – 2 ) = 5( x + 3)
Question
Not Answered
Updated 90 days ago|3/26/2018 3:45:04 AM
1 Answer/Comment
4( x - 2 ) = 5( x + 3)
(4)(x)+(4)( - 2)=(5)(x)+(5)(3)
4x - 8 = 5x + 15
4x - 8 = 15 - 5x
- x - 8 = 15
- x = 15 + 8
- x = 23
x = 23/-1
x = - 23
Added 90 days ago|3/26/2018 3:45:00 AM
This answer has been confirmed as correct and helpful.
solve for x (show steps)4( x – 2 ) = 5( x + 3)
Weegy: 4( x – 2 ) = 5( x + 3); 4x - 8 = 5x + 15; 4x - 5x = 15 + 8; -x = 23; x = -23 (More)
Question
Expert Answered
Updated 7/28/2014 1:05:54 PM
0 Answers/Comments
27,015,263 questions answered
*
Get answers from Weegy and a team of really smart lives experts.
Popular Conversations
What's 3 * 4
Weegy: Synonyms for the word "say" which are bigger in length and in impact, are communicate, ...
6/16/2018 8:51:59 PM| 2 Answers
Solve for x 3x + 3 - x + (-7) > 6 A. x > 2.5 B. x > ...
Weegy: (3x + 1) + 8 = 4(x + 9), 3x + 9 = 4x + 36, 3x - 4x = 36 - 9, -x = 27, x = -27 User: Solve this ...
6/21/2018 5:41:04 PM| 2 Answers
When adding a suffix that begins with a consonant, the general rule ...
Weegy: If the ending begins with a consonant, the spelling of the root word is usually not altered.
6/21/2018 8:43:17 PM| 2 Answers
S
L
Points 265 [Total 283] Ratings 0 Comments 195 Invitations 7 Offline
S
L
R
Points 145 [Total 296] Ratings 1 Comments 5 Invitations 13 Offline
S
L
Points 135 [Total 135] Ratings 0 Comments 135 Invitations 0 Offline
S
R
L
R
P
R
P
R
Points 66 [Total 734] Ratings 0 Comments 6 Invitations 6 Offline
S
1
L
L
P
R
P
L
P
P
R
P
R
P
R
P
P
Points 62 [Total 13329] Ratings 0 Comments 62 Invitations 0 Offline
S
L
1
R
Points 34 [Total 1450] Ratings 2 Comments 14 Invitations 0 Offline
S
L
Points 10 [Total 187] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 10 [Total 13] Ratings 0 Comments 10 Invitations 0 Offline
S
Points 10 [Total 10] Ratings 0 Comments 0 Invitations 1 Offline
S
Points 2 [Total 2] Ratings 0 Comments 2 Invitations 0 Offline
* Excludes moderators and previous
winners (Include)
Home | Contact | Blog | About | Terms | Privacy | © Purple Inc.